Concentrated Growth Factor Enhanced Fat Graft Survival: A Comparative Study. Issue 7 (July 2018) - Hu, Yun; Jiang, Yichen; Wang, Muyao; Tian, Weidong; Wang, Hang
Abstract : BACKGROUND: Concentrated growth factors (CGFs) belong to a new generation biomaterials that concentrate large number of growth factors and CD34 + stem cells in small volume of plasma. OBJECTIVE: The purpose of this study was to evaluate the impact of the new technique, CGF, on fat graft survival, which compared with platelet-rich plasma (PRP) and platelet-rich fibrin (PRF). MATERIALS AND METHODS: Nude mice received fat graft were divided into PRP group, PRF group, CGF group, and saline. The grafts were volumetrically and histologically evaluated at 4, 8, and 12 weeks after fat grafting. In vitro growth factor levels in PRP, PRF, and CGF were compared using enzyme-linked immunoassay method. Cell count and real-time polymerase chain reaction were used to evaluate the impact of CGF in medium on human adipose-derived stem cell (hADSC) proliferation and vascular differentiation, respectively. RESULTS: Fat graft weight was significantly higher in the CGF group than those in the other groups, and histologic evaluation revealed greater vascularity, fewer cysts, and less fibrosis. Adding CGF to the medium maximally promoted hADSC proliferation and expressing vascular endothelial growth factor and PECAM-1. CONCLUSION: In this preliminary study, CGF treatment improved the survival and quality of fat grafts.